Mining waste contaminated lands: an uphill battle for improving crop productivity - B M Kumar (Brawijaya University, 2013)
Mining drastically alters the physico-chemical and biological environment of the landscape. Low organic matter content, unfavourable pH, low water holding capacity, salinity, coarse texture, compaction, siltation of water bodies due to wash off of mineral overburden dumps, inadequate supply of plant nutrients, accelerated erosion, acid generating materials, and mobilization of contaminated sediments into the aquatic environment are the principal constraints experienced in mining contaminated sites. A variety of approaches have been considered for reclaiming mine wastes including direct revegetation of amended waste materials, top soiling, and the use of capillary barriers. The simplest technology to improve crop productivity is the addition of organic amendments. Biosolids and animal manure can support revegetation, but its rapid decomposition especially in the wet tropics, necessitates repeated applications. Recalcitrant materials such as “biochars”, which improve soil properties on a long term basis as well as promote soil carbon sequestration, hold enormous promise. An eco-friendly and cost-effective Microbe Assisted Phytoremediation system has been proposed to increase biological productivity and fertility of mine spoil dumps. Agroforestry practices may enhance the nutrient status of degraded mine spoil lands (facilitation). N-fixing trees are important in this respect. Metal tolerant ecotypes of grasses and calcium-loving plants help restore lead, zinc, and copper mine tailings and gypsum mine spoils, respectively. Overall, an integrated strategy of introduction of metal tolerant plants, genetic engineering for enhanced synthesis and exudation of natural chelators into the rhizosphere, improvement of rhizosphere, and integrated management including agroforestry will be appropriate for reclaiming mining contaminated lands.